Prevalence of sleep disorders among physicians and nurses during COVID-19 pandemic - Vladislav E. Karnaukhov; Ekaterina A. Narodova; Irina V. Demko; Natalia A. Shnayder; Valeriya V. Narodova; Diana V. Dmitrenko; Regina F. Nasyrova (Russian Open Medical Journal)
The objective of our review was to analyze studies of prevalence sleep disorders among medical workers during COVID-19 pandemic. Material and Methods — Overall, during the analyzed period, studying domestic and foreign databases, we identified 94 publications on the development of sleep disorders among medical personnel working during COVID–19 pandemic in 2000-2021. However, only 88 of these publications complied with the objective of the review. We included 75 full-text publications in this review. Results — Physicians and nurses during COVID-19 pandemic do not have the opportunity to take therapy aimed at combating the symptoms of sleep disorders, due to the need to maintain sufficient attention and the risk of developing excessive drowsiness while on duty in a COVID -19 hospital. The latter can have a negative impact on their professional activities. Thus, this problem certainly requires professional psychotherapeutic correction. Unfortunately, not all medical institutions have such specialists. Conclusion — Based on the literature review, we found out that health care workers have a high risk of developing sleep disorders. This can include violations of the circadian rhythm, a decrease in the quality and duration of night sleep, daytime hypersomnia caused by shift work in a hospital. An additional factor affecting the frequency and severity of sleep disorders in healthcare workers (physicians and nurses) is chronic stress, the importance of which has increased during the COVID-19 pandemic. Currently, the above problem has not been completely solved and requires research in this area and the development of new programs to help medical personnel.